2020
DOI: 10.1093/cid/ciaa1198
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors for Coronavirus Disease 2019 (COVID-19) Death in a Population Cohort Study from the Western Cape Province, South Africa

Abstract: Background Risk factors for COVID-19 death in sub-Saharan Africa and the effects of HIV and tuberculosis on COVID-19 outcomes are unknown. Methods We conducted a population cohort study using linked data from adults attending public sector health facilities in the Western Cape, South Africa. We used Cox-proportional hazards models adjusted for age, sex, location and comorbidities to examine the association between HIV, tuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
405
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 481 publications
(431 citation statements)
references
References 28 publications
18
405
4
4
Order By: Relevance
“…This increased mortality risk with HIV infection manifests itself in different parts of the patient pathway in different settings. Thus in the South African study cited above, the increased mortality risk was most apparent in non-hospitalised individuals; (19) in the NYC study, the big difference was in diagnosis and hospitalisation rates -once admitted mortality was similar to non-HIV-infected individuals; (12) in the UK study, in which hospitalisation was an entry criterion, mortality rates were found to be significantly higher in PLWH after admission. 21It does therefore appear reasonable to take HIV status into account in developing policies and practice, but do we treat all PLWH the same?…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This increased mortality risk with HIV infection manifests itself in different parts of the patient pathway in different settings. Thus in the South African study cited above, the increased mortality risk was most apparent in non-hospitalised individuals; (19) in the NYC study, the big difference was in diagnosis and hospitalisation rates -once admitted mortality was similar to non-HIV-infected individuals; (12) in the UK study, in which hospitalisation was an entry criterion, mortality rates were found to be significantly higher in PLWH after admission. 21It does therefore appear reasonable to take HIV status into account in developing policies and practice, but do we treat all PLWH the same?…”
Section: Discussionmentioning
confidence: 91%
“…However, in the absence of better data, these papers contributed to a general consensus that HIV does not predispose to more severe disease or higher mortality; as one author put it, there is an "… under-representation of people living with HIV (PLWH) among severe COVID-19 cases". (18) More recently, four studies have been published with much larger numbers of cases that appear to overturn this relatively benign paradigm, the papers by Boulle et al, (19) Bhaskaran et al, (20) The Tesoreiro et al study, (12) summarised above also reported mortality risk. Interestingly, in their study, the mortality risk once patients were hospitalised was similar to non-HIV infected individuals, but taking increased diagnosis and admission rates into account, the standardized mortality ratio for PLWH was higher than the general population (1.23; 95% CI: 1.13-1.48).…”
Section: Does Hiv Increase the Risk Of Severe Infection With Adverse mentioning
confidence: 99%
“…In the South African study, lower CD4+ T cell counts (measured during the COVID-19 episode) were associated with mortality, but this could be a result of, rather than causing, severe disease ( Table 2). There was no difference in outcomes by HIV viral load, although viral load data was incomplete and numbers with unsuppressed viral loads were small [18]…”
Section: Risk Of Death and Hospitalisation In Relation To Cd4+ T Cellmentioning
confidence: 91%
“…We identified 1,908 records and included 19 studies in our final qualitative analysis ( Figure 1). Seventeen studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] were peer-reviewed and two were preprints [27,28]. Quality appraisal is included in Tables 1, S2 and S3.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation